Acoustic and thermal performance of polypropylene nonwoven fabrics for insulation in buildings. (1st June 2022) - Karimi, Faezeh; Soltani, Parham; Zarrebini, Mohammad; Hassanpour, Ali
Abstract: Thermal insulation and acoustic absorption materials play a significant role in the characteristics of energy-saving and comfortable modern buildings. However, these two types of materials are generally developed independently. This study highlights the potential of lightweight polypropylene nonwoven fabrics for building applications and investigates how fabric structure affects thermal and acoustical properties. An industrial-scale melt spinning machine was used to produce polypropylene fibers at linear densities of 1.4 and 1.8 dtex. A semi-industrial needle punching line was used to fabricate nonwoven samples with three thicknesses (2, 3, and 4 cm), four porosities (0.83, 0.88, 0.93, and 0.96), and different in- and through-plane fiber orientation distributions. Totally, 31 samples were produced and their sound absorption and thermal insulation performance were assessed using impedance tube and guarded hot plate techniques. Accordingly, the thermal conductivity ( K e f f ) and sound absorption average (SAA) of the samples could be engineered in the range of 0.0270–0.0404 W m -1 K -1 and 0.270–0.675, respectively. It was found that fabrics made of finer fibers provide superior acoustic absorption and thermal insulation performance. An increase in through-plane fiber orientation adversely affected the thermal insulation properties, while its effect on acoustic properties depends on the porosity of samples and the sound frequency. The results of statistical analysis showed that in-plane fiber orientation does not have a significant effect on sound absorption behavior, except at frequencies between 4000 and 6300 Hz. It was also found that in-plane fiber orientation does not significantly affect the thermal insulation properties. The best acoustic and thermal performance were achieved by fibrous samples of layered structure made of 1.4 dtex fibers with a thickness of 3 cm ( K e f f =0.0278 W m -1 K - 1, SAA = 0.552) and 4 cm ( K e f f =0.0277 W m -1 K -1, SAA = 0.675). The performance of these samples was compared with some commercial products and literature data. The results pointed to the superior acoustic and thermal properties of the designed samples. Highlights: Nonwoven fabrics having high sound absorption and thermal resistance were produced. Samples successfully compete with commercial glasswool and rockwool products. X-ray micro-computed tomography was used to investigate the 3D structure of samples. Effect of structural parameters on thermal and acoustical properties was studied. Increase in TP fiber orientation adversely affects thermal insulation properties.